1983
DOI: 10.1177/036354658301100203
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of soccer injuries and their relation to training and team success

Abstract: One hundred-eighty players in a male soccer senior division of 12 teams were observed prospectively for 1 year to study the risk of soccer injuries in relation to exposure and to establish the connection between training, injuries, and team success. Totally, more than 100 hours of practice were analyzed. All injuries were examined by the same orthopaedic surgeon. On the average, each team played 36 games and had 95 practice sessions with 66% attendance of selected players. A direct correlation was noted betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
115
4
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(136 citation statements)
references
References 9 publications
(2 reference statements)
11
115
4
6
Order By: Relevance
“…The relatively high incidence of injuries during training was probably due to the bad technique, low fitness and large amount of over training by the high level of achievement footballers. Zelisko et al (1982), Ekstrand et al (1983) and Maughan & Miller (1983) also reported training related injuries in footballers, basketballers and marathon runners and ascribed them to the wrong techniques and poor fitness level of athletes. While comparing the occurrence of injuries between lower and upper limbs, no signifancant differences of injuries were found between the low and the high level of achievement footballers.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high incidence of injuries during training was probably due to the bad technique, low fitness and large amount of over training by the high level of achievement footballers. Zelisko et al (1982), Ekstrand et al (1983) and Maughan & Miller (1983) also reported training related injuries in footballers, basketballers and marathon runners and ascribed them to the wrong techniques and poor fitness level of athletes. While comparing the occurrence of injuries between lower and upper limbs, no signifancant differences of injuries were found between the low and the high level of achievement footballers.…”
Section: Discussionmentioning
confidence: 99%
“…In 1983, Ekstrand et al 6 found that a group of elite soccer teams randomly selected for an intervention of warming up and stretching before exercise; using leg guards and special shoes; taping ankles; and undergoing controlled rehabilitation, education, and close supervision had 75% fewer injuries than the control group. One other RCT and a quasi-experimental study also supported this conclusion, 7,8 and in both studies, at least warming up was a co-intervention. Clinical evidence suggesting that stretching before exercise does not prevent injuries has also been reported.…”
mentioning
confidence: 80%
“…Conversely, other investigations have not found [39] , while others have demonstrated a decreased risk among higher-skill level soccer players than their lower-skill level counterparts [43,47] . Other variables likely contribute to such differences seen between the different skill level cohorts, such as more match exposure and higher collective numbers of athlete-exposures [42] , higher match-to-training ratio [48] , and a lower warm-up or stretching period [48][49][50] .…”
Section: Anthropomorphic Measuresmentioning
confidence: 99%